2002
DOI: 10.1247/csf.27.139
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression of Type I and Type III Collagen by Mechanical Stretch in Anterior Cruciate Ligament Cells

Abstract: ABSTRACT. Mechanical stretch affects the healing and remodeling process of the anterior cruciate ligament (ACL) after surgery in important ways. In this study, the effects of mechanical stress on gene expression of type I and III collagen by cultured human ACL cells and roles of transforming growth factor (TGF)-β1 in the regulation of mechanical strain-induced gene expression were investigated. Uniaxial cyclic stretch was applied on ACL cells at 10 cycles/min with 10% length stretch for 24 h. mRNA expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
104
4

Year Published

2005
2005
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(115 citation statements)
references
References 27 publications
6
104
4
Order By: Relevance
“…In contrast to the biaxial stretching effects as described above, 10% cyclic uniaxial stretching of ACL fibroblasts at 0.33 Hz for 24 h increased the expression of both collagen types I and III mRNA levels; the ratios of stretch to control values of type I and type III collagen were 1.6 and 2.7, respectively (Kim et al, 2002). In parallel, TGF-β1 protein in the medium was increased in response to stretching.…”
Section: Regulation Of Gene Expression In Fibroblasts By Mechanical Lmentioning
confidence: 67%
“…In contrast to the biaxial stretching effects as described above, 10% cyclic uniaxial stretching of ACL fibroblasts at 0.33 Hz for 24 h increased the expression of both collagen types I and III mRNA levels; the ratios of stretch to control values of type I and type III collagen were 1.6 and 2.7, respectively (Kim et al, 2002). In parallel, TGF-β1 protein in the medium was increased in response to stretching.…”
Section: Regulation Of Gene Expression In Fibroblasts By Mechanical Lmentioning
confidence: 67%
“…Because the amount of collagens I and III are reduced by suppressing TGF-β1 released by ligament cells, TGF-β1 is involved in ligament regeneration. As a result, when ligament cells were stretched, levels of TGF-β1 released by the cells also increased in order to activate the regeneration of ligament cells (9). In this way, numerous studies have found that mechanical stretching affects cellular growth.…”
Section: Effects Of Mechanical Stretching On Cultured Cellsmentioning
confidence: 99%
“…This happens through mechanotransduction pathways affecting the anabolic as well as the catabolic responses (Brown et al, 1998;Hsieh et al, 2000;Zeichen et al, 2000). It has been reported that the cells sense the applied strain (Chiquet, 1999;Chiquet et al, 2003) and regulate the synthesis of matrix proteins (Arnoczky et al, 2002;Skutek et al, 2003;Miller et al, 2005), the gene expression of proteoglycans and collagen (Robbins and Vogel, 1994;Kim et al, 2002;Hsieh et al, 2000), the alignment and density of the collagenous matrix (Pins et al, 1997;Wang et al, 2001;Wang et al, 2003a) as well as the expression of several growth factors (Skutek et al, 2001;Yang et al, 2004;Olesen et al, 2006). Studies examining the influence of mechanical loading on the regulation of the biosynthesis of connective soft tissues demonstrated that the strain magnitude, strain frequency, strain rate and strain duration of cells influence the cellular biochemical responses (Skutek et al, 2003;Arnoczky et al, 2002;Yang et al, 2004) and the mechanical properties of collagen fascicles (Yamamoto et al, 2002;Yamamoto et al, 2003;Yamamoto et al, 2005).…”
Section: Introductionmentioning
confidence: 99%